Attracting, recruiting and retaining nurses and care workers working in care homes: the need for a nuanced understanding informed by evidence and theory. (1st July 2020) - Devi, Reena; Goodman, Claire; Dalkin, Sonia; Bate, Angela; Wright, Judy; Jones, Liz; Spilsbury, Karen
Abstract: The care home sector relies on nurses and care workers to deliver care to residents living with frailty and complex needs. However, attracting, recruiting and retaining staff is one of the biggest challenges facing this sector. There is evidence available that describes factors that influence staff decisions to join and/or remain in the care home workforce, for example, individual rewards (such as feeling valued at work or training opportunities), relationships with colleagues and residents, supportive management or working arrangements (including flexible hours). However, it is less clear how different strategies are informed by evidence to improve recruitment and retention. Care homes are heterogeneous in terms of their size, staffing levels and mix, staff age groups, geographical location and working conditions. What matters to different members of the care home workforce will vary across nurses and care workers of different ages and levels of qualification or experience. Recognising this diversity is key: understanding how to attract, recruit and retain staff needs to discriminate and offer solutions that address this diversity. This important area of practice does not lend itself to a 'one-approach-fits-all' solution. This commentary provides a brief overview of known workforce challenges for the care home sector and argues for studies that use empirical evidence to test different theories of what might work for different staff, how and why, and in different circumstances.